CHALLENGES AND INNOVATIVE APPROACHES TO TEACHING GRAMMAR TO ENGLISH FOR SPECIFIC PURPOSES (ESP) LEARNERS - Mukhiddinova Omina (Journal Park Publishing, 2023)
This article explores the complex pedagogical and learner challenges associated with teaching grammar to English for Specific Purposes (ESP) learners. Recognizing that ESP learners have distinct, vocationally oriented language needs, the paper acknowledges the limitations of traditional methods that prioritize abstract rules and decontextualized exercises. It highlights the necessity for more tailored instruction that effectively meets the learners' specific professional or academic contexts. Furthermore, it considers learners' difficulties, such as the perceived complexity of English grammar and the lack of opportunities for practice and feedback. The article then proposes innovative pedagogical strategies to address these challenges, emphasizing the importance of contextualized, practical, and engaging instruction. These approaches include a genre-based approach, the integration of grammar with other language skills, the use of corpora, a discovery-based learning method, and the incorporation of technology.
Keywords: English for Specific Purposes (ESP), Grammar Instruction, Pedagogical Challenges, Learner Challenges, Innovative Approaches, Genre-Based Approach, Corpora, Discovery-Based Learning, Contextualized Instruction, Technology in Education.